2016
DOI: 10.18869/acadpub.nfsr.3.4.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Atmosphere Packaging on Aril Physico-chemical and Microbial Properties of Two Pomegranate Cultivars (Punica granatum L.) Grown in Iran

Abstract: A B S T R A C TBackground and Objectives: Edible parts of pomegranate fruits are a rich source of bioactive compounds. The present research examines the effect of modified atmosphere packaging on the fruit physico-chemical and microbial properties of two commercial pomegranate cultivars grown in Iran. Materials and Methods:The arils were packaged and stored under four different atmospheres. All of the packaged samples were stored at 4 °C for 15 days. Results:The results revealed an increase in total acidity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Another study by Hussein, Caleb, Jacobs, Manley and Opara [30] documented the increased CO 2 for fresh pomegranate arils after 3 days of storage at 5 • C. However, the extreme increased CO 2 may deteriorate the quality attributes, such as increased weight loss, nutritional loss, and sensorial attributes of the final product. Thus, previous studies recommended gas composition of 5% O 2 and 0-5% CO 2 at 5 • C, 3-5% O 2 and 5-10% CO 2 at 5 • C, and 10% O 2 + 15% CO 2 to extend the shelf-life of ready-to-eat fresh-cut fruits and vegetables [15,16]. Therefore, we concluded that the concentrations of O 2 and CO 2 remained under desired gas composition of the storage atmosphere and maintained the freshness of the pomegranate arils.…”
Section: Package Headspace Gas Composition (O 2 and Co 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Hussein, Caleb, Jacobs, Manley and Opara [30] documented the increased CO 2 for fresh pomegranate arils after 3 days of storage at 5 • C. However, the extreme increased CO 2 may deteriorate the quality attributes, such as increased weight loss, nutritional loss, and sensorial attributes of the final product. Thus, previous studies recommended gas composition of 5% O 2 and 0-5% CO 2 at 5 • C, 3-5% O 2 and 5-10% CO 2 at 5 • C, and 10% O 2 + 15% CO 2 to extend the shelf-life of ready-to-eat fresh-cut fruits and vegetables [15,16]. Therefore, we concluded that the concentrations of O 2 and CO 2 remained under desired gas composition of the storage atmosphere and maintained the freshness of the pomegranate arils.…”
Section: Package Headspace Gas Composition (O 2 and Co 2 )mentioning
confidence: 99%
“…Likewise, other studies recommended the gas composition of 5% O 2 and 0-5% CO 2 at 5 • C and 3-5% O 2 and 5-10% CO 2 at 5 • C during MAP [15]. Another study recommended the 10% O 2 + 15% CO 2 to extend the shelf-life of ready-to-eat pomegranate arils [16]. However, the use of gas composition is purely depending on the type of produce, packaging material, and storage temperature.…”
Section: Introductionmentioning
confidence: 99%